OPTIMIZATION OF CRIMINAL ACTION OF CROSS-TRAFFIC ACCIDENTAL LAWS IN THE LAW REGION EAST LUWU POLRES - Sarifuddin; Hambali Thalib; Mulyati Pawennai (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal